2023
DOI: 10.1371/journal.pone.0281023
|View full text |Cite
|
Sign up to set email alerts
|

Digital inclusive finance & the high-quality agricultural development: Prevalence of regional heterogeneity in rural China

Abstract: Developing digital inclusive finance is one of the most effective ways to alleviate financial exclusion in the agriculture sector. For empirical investigation, data from 30 provinces of Rural China is collected from the period 2011 to 2020. The study constructs five dimensions and 22 indicators in total to critically conduct the impact of digital inclusive finance on high-quality agricultural development. The level of agricultural development is measured by entropy weight TOPSIS, and the impact of digital incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…pointed out that the development of digital inclusive finance has significantly promoted the level of rural revitalization, and this promotion is mainly reflected in the four directions of rural revitalization: rural civilization, industrial prosperity, affluent life, and ecological livability. Zhang et al (2023) believe that China's rural revitalization has five demands, namely industrial prosperity and ecological livability, and digital inclusive finance can meet the demands of rural revitalization in many aspects, such as reducing the financial exclusion of traditional finance, promoting rural households, innovation, enhanced risk management, and control capabilities, etc. Chen et al ( 2022) mainly examined the impact of digital economy on rural revitalization and further conducted the mediating effect of industrial upgrading, which concluded that the digital economy would promote the rural industrial prosperity and thus eventually bringing about rural revitalization.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…pointed out that the development of digital inclusive finance has significantly promoted the level of rural revitalization, and this promotion is mainly reflected in the four directions of rural revitalization: rural civilization, industrial prosperity, affluent life, and ecological livability. Zhang et al (2023) believe that China's rural revitalization has five demands, namely industrial prosperity and ecological livability, and digital inclusive finance can meet the demands of rural revitalization in many aspects, such as reducing the financial exclusion of traditional finance, promoting rural households, innovation, enhanced risk management, and control capabilities, etc. Chen et al ( 2022) mainly examined the impact of digital economy on rural revitalization and further conducted the mediating effect of industrial upgrading, which concluded that the digital economy would promote the rural industrial prosperity and thus eventually bringing about rural revitalization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital inclusive finance can make up for the shortcomings of traditional finance and provide services for the country's agricultural economy in terms of availability, convenience, and comprehensiveness (Wang and Mai, 2022). Digital technology has reduced the transaction costs of rural finance on both the supply side and the demand side, not only breaking through the geographical restrictions of traditional financial outlets, but also significantly reducing rent-seeking costs (Zhang et al, 2023). Secondly, ecological livability is the top priority of rural revitalization.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…This development has enabled lowcost, high-efficiency fund matching to some extent, addressing the shortcomings of traditional financial services. From the supply-side perspective, it has enhanced the accessibility of financial services in agricultural sectors [28], providing ample capital elements for agricultural development and rural revitalization. Digital inclusive finance may directly affect agricultural development through its inherent characteristics and advantages.…”
Section: Direct Effects Of Digital Inclusive Finance On Agricultural ...mentioning
confidence: 99%
“…Previous studies have shown that the convergence of rural industries and modern finance is an important aspect of rural industry convergence [33][34][35]. At the same time, the support of finance as an important source of capital for the development of rural industries is also crucial for the success of the deep convergence of rural industries.…”
Section: Increase Support For Agriculture-related Financementioning
confidence: 99%